2002
DOI: 10.2307/3088363
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Kin on Child Mortality in Rural Gambia

Abstract: This is an electronic version of an Article published in Demography, 39 (1). pp. 43-63

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…In contrast to the analysis of child mortality (Sear et al, 2000(Sear et al, , 2002, the effects of the husband's mother were more important than those of the woman's mother. Somewhat unexpectedly, the husband's father also had a slight positive effect on female fertility.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…In contrast to the analysis of child mortality (Sear et al, 2000(Sear et al, , 2002, the effects of the husband's mother were more important than those of the woman's mother. Somewhat unexpectedly, the husband's father also had a slight positive effect on female fertility.…”
Section: Discussionmentioning
confidence: 46%
“…Elder siblings are often assigned as nursemaids to younger children in West African societies (Thompson & Rahman, 1967;Whittemore & Beverly, 1989). We found that the presence of a woman's elder daughters increased the survival chances of her children (Sear et al, 2002) and their nutritional status (unpublished data). A recent study of a Moroccan Berber population has shown that probable helpers (i.e.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies of contemporary populations usually use short-term and partial outcomes such as death during childhood e.g. 3 or the probability of giving birth within an observation period e.g. 4 rather than direct and detailed measurements of survival and reproduction over the whole life-course.…”
Section: Studying Reproductive Success In Humansmentioning
confidence: 99%
“…Because of the longitudinal nature of the dataset, a number of records from the same woman (either birth intervals or children) were included in each analysis. Multi-level models are able to control for this non-independence of data points, with the inclusion of a mother-level random effect (see Sear et al, 2003;Sear et al, 2002 for further details of this technique applied to this dataset).…”
Section: Length Of Birth Intervals and Child Mortalitymentioning
confidence: 99%